Linezolid treatment of shunt-related cerebrospinal fluid infections in children Clinical article - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2010)
Object. The emergence of multidrug-resistant bacteria as a cause of ventriculoperitoneal (VP) shunt infection is a disconcerting phenomenon that often requires the use of alternative antimicrobial agents due to resistance against commonly used medications. Linezolid, a member of a new class of antimicrobial agents, has good activity against virtually all important gram-positive pathogens, including multidrug-resistant gram-positive pathogens. The object of this article is to report a single-center experience with linezolid treatment in 6 young patients with VP shunt infections caused by drug-resistant strains. Methods. The authors reviewed the records of 6 pediatric patients who developed VP shunt infection and in whom initial antimicrobial treatment regimens, including vancomycin, either failed or were associated with vancomycin-resistant enterococcus. All 6 patients were treated at their hospital between July I, 2008, and June 29, 2009. The patients' demographic and clinical characteristics, underlying diseases, clinical manifestations, laboratory results, and various treatment modalities used before linezolid therapy were evaluated. Results. The 6 patients included were 2 boys and 4 girls with a mean (+/- SD) age of 11.83 +/- 12 months (range 4-36 months). Five patients had acquired an infection within 4 months (mean 7.50 +/- 13.51 months, range 1-35 months) after shunt insertion. Four patients were treated with external ventricular drainage. Two patients parents refused to allow shunt removal and placement of an external ventricular drain. The CSF was clear of bacterial growth within a mean of 3.67 +/- 1.36 days (range 2-6 days) after initiation of linezolid treatment. The mean duration of linezolid treatment was 18.17 +/- 3.31 days (range 14-21 days). Microbiological clearance of CSF and clinical cure were achieved in all patients. No laboratory or clinical side effects were observed during the treatment period. The mean length of hospital stay was 22.8 +/- 4.96 days (range 17-28 days). Conclusions. Linezolid could be an appropriate treatment alternative in children with ventriculostomy-related CSF infections caused by drug-resistant strains, including cases in which shunt removal is not an option. Well-designed prospective studies providing additional information on linezolid levels in plasma and CSF are necessary to confirm the authors' observations. (DOI: 10.3171/2009.12.PEDS09421)
Keywords: linezad; ventriculoperitoneal shunt; infection; multidrug resistance; RESISTANT ENTEROCOCCUS-FAECIUM; NERVOUS-SYSTEM INFECTIONS; STAPHYLOCOCCUS-AUREUS; BACTERIAL BIOFILMS; VANCOMYCIN; MENINGITIS; VENTRICULITIS; EXPERIENCE; MANAGEMENT; SUSCEPTIBILITY